Coupling Coordination Relationship of Land Ecological Security and Prosperity Process at Border Areas in Guangxi Zhuang Autonomous Region from 2000 to 2020 - Liu Shaokun; Huang Ronghua; Zhang Liguo; Wang Pengcheng (Shuitu baochi tongbao)
[Objective] The effect of land ecological security at border areas in Guangxi Zhuang Autonomous Region, and the process for improving border areas and enriching people were evaluated scientifically, and the coupling coordination mechanism was revealed in order to provide a reference for promoting border revitalization and regional coordinated development. [Methods] The study was conducted for the eight counties in the border areas of Guangxi. We analyzed the spatial-temporal characteristics of the coupling coordination between land ecological security and the process of prospering the frontier and enriching people in Guangxi border areas from 2000 to 2020. We used the entropy weight TOPISIS comprehensive evaluation method and coupling coordination model. [Results] ① The land ecological security index of border areas gradually increased over time, with the overall ecological security index increasing from 0.213 to 0.728. The land ecological security of each county exhibited different growth rates. The regional differences decreased, showing an overall spatial pattern of “high in the north and south, low in the middle”. ② The overall coordination level of the process of prospering the frontier and enriching the people has rose from 0.176 to 0.631, following a pattern of “decrease-increase”. Regional differences were not obvious. The grade difference of the process of prospering the frontier and enriching the people in each county was not obvious, and the overall pattern changed little. The development advantages of Pingxiang and Dongxing City, which are important national ports, become more and more obvious. ③ The coupling coordination degree of the land ecological security system and the process system of prospering the frontier and enriching the people was increasing day by day, rising from 0.440 to 0.823, and the coupling degree of the two followed a pattern of “decrease-increase”. The spatial feature gradually evolved from “overall dispersion” to “high in the north and south, low in the middle”. Driven by the “dual-core” radiation of Pingxiang and Dongxing City, the coordination type was gradually evolving from mild disorder and imminent disorder to primary coordination. [Conclusion] The national strategy of prospering the frontier, enriching the people, and ecologically protecting the environment requires strengthening the innovation of border policy, coordinating the superposition effect of multiple factors, and continuously improving the ecological security and happiness index of border residents.